2020
DOI: 10.1002/cb.1850
|View full text |Cite
|
Sign up to set email alerts
|

Organic defaults in online‐shopping: Immediate effects but no spillover to similar choices

Abstract: Changing defaults—the preselection that becomes effective without active choice—is becoming a prominent policy tool, after having been proven to be effective in areas as varied as retirement savings, organ donation and product customization. Yet, little is known about how default effects spill over to subsequent similar behaviors. In an online shopping scenario, we found standard default effects on the share of organically produced products in the overall selection of products. These effects did not spill over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 107 publications
(135 reference statements)
5
17
0
Order By: Relevance
“…In Study 1, we found that the default nudge had a significant effect on the number of nudged healthy choices in an online supermarket setting. This illustrates that nudges can successfully be implemented in online choice settings, which is in line with current evidence (Antonides & Welvaarts, 2020;Coffino, Udo, & Hormes, 2020;Kuhn et al, 2021). Moreover, we found that goal strivings and autonomous motivation also had a positive main effect on the number of nudged healthy choices.…”
Section: Discussion Studysupporting
confidence: 90%
See 4 more Smart Citations
“…In Study 1, we found that the default nudge had a significant effect on the number of nudged healthy choices in an online supermarket setting. This illustrates that nudges can successfully be implemented in online choice settings, which is in line with current evidence (Antonides & Welvaarts, 2020;Coffino, Udo, & Hormes, 2020;Kuhn et al, 2021). Moreover, we found that goal strivings and autonomous motivation also had a positive main effect on the number of nudged healthy choices.…”
Section: Discussion Studysupporting
confidence: 90%
“…That is, across the behavioral domains of healthy eating and sustainability, and thus across pro-self and pro-social nudges, we found that goal strivings and autonomous motivation had a significant main effect on the behavior of interest. This corroborates findings from studies on the role attitudes in nudges' effectiveness (Kaiser et al, 2020;Kuhn et al, 2021;Taube & Vetter, 2019;Vetter & Kutzner, 2016), which have also revealed main effects only on behavioral outcomes. Controlled motivation did not affect our behavioral outcomes in Study 1 and 3, while it significantly predicted sustainable behavior in Study 2, but with negligible predictive power and little practical significance.…”
Section: Discussion Studysupporting
confidence: 89%
See 3 more Smart Citations